2008
DOI: 10.1111/j.1745-7262.2008.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of t-complex testis expressed gene 5 transcripts in the testis of sterile t-haplotype mutant mouse

Abstract: We established that mutations that occur in the Tctex5 long transcript of the t-haplotype mice are important for normal sperm function, whereas the short transcript of Tctex5 might have a conserved function among different tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…PPP1R11 (Protein Phosphatase 1 Regulatory Subunit 11) was originally described to interact with and inhibit protein phosphatase 1 activity (Zhang et al, 1998) . It also has another name, TcTex5 (T-Complex-Associated-Testis-Expressed 5), and it was implied that mutation of TcTex5 is associated with a mouse sperm motility abnormality in sterile t-haplotype mutant mice (Han et al, 2008; Pilder et al, 2007). However, its E3 ligase activity has never been described.…”
Section: Discussionmentioning
confidence: 99%
“…PPP1R11 (Protein Phosphatase 1 Regulatory Subunit 11) was originally described to interact with and inhibit protein phosphatase 1 activity (Zhang et al, 1998) . It also has another name, TcTex5 (T-Complex-Associated-Testis-Expressed 5), and it was implied that mutation of TcTex5 is associated with a mouse sperm motility abnormality in sterile t-haplotype mutant mice (Han et al, 2008; Pilder et al, 2007). However, its E3 ligase activity has never been described.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the different isoforms of PPP1R11 (also known as TCTEX5) were found to be expressed in most mouse tissues with high expression in testis, epididymis, and in the head and tail regions of spermatozoa (Han et al, 2007). In a subsequent study, it was shown that mutations in the long transcript of PPP1R11 were associated with normal sperm function (Han et al, 2008). The authors concluded that PPP1R11 plays important roles in sperm motility and spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell protein lysates were generated using RIPA Lysis Buffer (Beyotime, China) and were added to PMSF (Beyotime) at a ratio of 100:1. Cellular proteins were extracted 48 h posttransfection, the number of cells was 10 [6]. Proteins were separated by SDS-PAGE and were transferred into polyvinylidene fluoride membranes (Millipore, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In our previous work, PPP1R11 (protein phosphatase 1 regulatory subunit 11) gene was significantly expressed in pigs after SS2 challenged [3]. The PPP1R11 gene is a member of the PPP (protein phosphatases) superfamily, which encodes protein inhibitor 3 (Inh3) to inhibit PP1, which regulates diverse cellular processes, such as cell cycle, transcription, protein synthesis and metabolism [4][5][6][7]. The role of PPP1R11 in immune response has been paid more attention than in other functions [8,9].…”
Section: Introductionmentioning
confidence: 99%